Fiz tv na internet: táticas de ocupação midiática - Carolina Fonseca Cotta (2010)
From the work of Michel de Certeau (2008), this study proposes to identify the tactics set by the subjects in achieving visibility and the media space of major media, as well as the importance of the other who watches, votes and allows, therefore, the transition of the productions from the Internet to the television. The interaction and the sociability, as defined by Erving Goffman (1985), George Herbert Mead (1993) and Georg Simmel (2002), stand out from the cunnings of the participants of FIZ TV, a project to promote brazilian audiovisual through convergence of media. Based on collaboration, FIZ TV made available space in television for young video producers - amateur or professional - but ordinary people that are out of that production chain, exhibit their production in a system based on votes and payment. The "little strokes" of these participants could be identified by analyzing the comments in Sr. Noir's Blog, interactive environment of the participants, and interviews with the main names of the project. getting to television. The resu lt is a series of practices designed, built and executed with a purpose.